Long-term Graft Rupture Rates After Combined ACL and Anterolateral Ligament Reconstruction Versus Isolated ACL Reconstruction: A Matched-Pair Analysis From the SANTI Study Group. Issue 11 (September 2021) - Sonnery-Cottet, Bertrand; Haidar, Ibrahim; Rayes, Johnny; Fradin, Thomas; Ngbilo, Cedric; Vieira, Thais Dutra; Freychet, Benjamin; Ouanezar, Herve; Saithna, Adnan
Background: Clinical studies have demonstrated significant advantages of combined anterior cruciate ligament and anterolateral ligament reconstruction (ACL+ALLR) over isolated ACL reconstruction (ACLR) with respect to reduced graft rupture rates, a lower risk of reoperation for secondary meniscectomy, improved knee stability, and higher rates of return to sports. However, no long-term studies exist. Purpose/Hypothesis: The purpose of this study was to compare the outcomes of isolated ACLR versus ACL+ALLR at long-term follow-up. The hypothesis was that patients who underwent combined procedures would experience significantly lower rates of graft rupture. Study Design: Cohort study; Level of evidence, 3. Methods: Patients undergoing primary ACL+ALLR between January 2011 and March 2012 were propensity matched in a 1:1 ratio to patients who underwent isolated ACLR during the same period. A combination of face-to-face and telemedicine postoperative follow-up was undertaken. At the end of the study period (March 2020), medical notes and a final telemedicine interview were used to determine whether patients had experienced any complications or reoperations. The Knee injury and Osteoarthritis Outcome Score, International Knee Documentation Committee score, Lysholm score, and Tegner score were collected for all patients. Graft survivorship was assessed using Kaplan-Meier analysis. Logistic regression was performed to account for the potential effect of activity level on graft rupture rates. Results: A total of 86 matched pairs were included in the study. The mean ± SD age was 32.2 ± 8.8 years (range, 22-67 years) in the ACL+ALLR group and 34.7 ± 8.5 years (range, 21-61 years) in the isolated ACLR group. The mean duration of follow-up was 104.33 ± 3.74 months (range, 97-111 months). Patients who underwent combined ACL+ALLR versus isolated ACLR experienced significantly better ACL graft survivorship (96.5% vs 82.6%, respectively; P = .0027), lower overall rates of reoperation (15.3% vs 32.6%; P < .05), and lower rates of revision ACLR (3.5% vs 17.4%; P < .05). Patients undergoing isolated ACLR were at >5-fold greater risk of graft rupture (odds ratio, 5.549; 95% CI, 1.431-21.511; P = .0132), regardless of their preinjury activity level. There were no significant differences between groups with respect to other complications or any clinically important differences in patient-reported outcome measures. Conclusion: Patients who underwent combined ACL+ALLR experienced significantly better long-term ACL graft survivorship, lower overall rates of reoperation, and no increase in complications compared with patients who underwent isolated ACLR. Further, patients who underwent isolated ACLR had a >5-fold increased risk of undergoing revision surgery at a mean follow-up of 104.3 months.